Correlation between forecasting and successful socialization of children with development disorders - AKHMETZYANOVA, A.I.; ARTEMYEVA, T.V. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACTThe purpose of the research was to study the indicators of children's socialization and their dependence on the ability to predict children with speech, hearing, vision, motor and emotional disorders. The research involved 438 children of 5-7 years old with and without developmental disorders who attend preschool institutions in Russia. The empirical study confirmed the existence of close correlations between forecasting indicators and methodological indicators that reflect compliance of children’s behavior with regulatory rules and children’s communicative interaction in free and organized activity. The research data can be used to adapt and support children with developmental disorders in educational institutions. RESUMENEl propósito de la investigación fue estudiar los indicadores de socialización de los niños y su dependencia de la capacidad de predecir en niños con trastornos del habla, audición, visión, motores y emocionales. La investigación involucró a 438 niños de 5-7 años con y sin trastornos del desarrollo que asisten a instituciones preescolares en Rusia. El estudio empírico confirmó la existencia de correlaciones cercanas entre los indicadores de pronóstico y los indicadores metodológicos que reflejan el cumplimiento del comportamiento de los niños con las normas reguladoras y la interacción comunicativa de los niños en la actividad libre y organizada.